Molecular motion of a nanoscopic moonlander via translations and rotations of triphenylphosphine on graphite - Anton Tamtögl; Marco Sacchi; Victoria Schwab; Michael M. Koza; Peter Fouquet (Communications Chemistry, 2024)
Abstract Mass transport at surfaces determines the kinetics of processes such as heterogeneous catalysis and thin-film growth, with the diffusivity being controlled by excitation across a translational barrier. Here, we use neutron spectroscopy to follow the nanoscopic motion of triphenylphosphine (P(C6H5)3 or PPh3) adsorbed on exfoliated graphite. Together with force-field molecular dynamics simulations, we show that the motion is similar to that of a molecular motor, i.e. PPh3 rolls over the surface with an almost negligible activation energy for rotations and motion of the phenyl groups and a comparably small activation energy for translation. While rotations and intramolecular motion dominate up to about 300 K, the molecules follow an additional translational jump-motion across the surface from 350-500 K. The unique behaviour of PPh3 is due to its three-point binding with the surface: Along with van der Waals corrected density functional theory calculations, we illustrate that the adsorption energy of PPh3 increases considerably compared to molecules with flat adsorption geometry, yet the effective diffusion barrier for translational motion increases only slightly. We rationalise these results in terms of molecular symmetry, structure and contact angle, illustrating that the molecular degrees of freedom in larger molecules are intimately connected with the diffusivity.